2016
DOI: 10.1002/col.22066
|View full text |Cite
|
Sign up to set email alerts
|

Digital printing of acrylic fabric with cationic dyes using conventional inkjet printer

Abstract: A special printing ink formulation based on cationic dyes is developed for digital printing of acrylic fabrics using a conventional inkjet printer. In order to investigate the contribution of color gamut boundary of printer colorants to printing efficiency, customized color targets containing 3164 color patches in 25 different hues were generated. The printed color patches were then fixed through steaming for 30 minutes followed by washing with hot soap and water and finally drying. To show the influence of dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The results revealed the dye was not degraded during the printing process, maintaining its properties in the object. Fashandi studied the actinic dyes that were printed by a conventional digital printer (Fashandi, 2016). The results revealed that the washing fastness of printed fabrics was comparable to that of traditional screen printing.…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed the dye was not degraded during the printing process, maintaining its properties in the object. Fashandi studied the actinic dyes that were printed by a conventional digital printer (Fashandi, 2016). The results revealed that the washing fastness of printed fabrics was comparable to that of traditional screen printing.…”
Section: Introductionmentioning
confidence: 99%